2017
DOI: 10.4172/2329-8863.1000294
|View full text |Cite
|
Sign up to set email alerts
|

The Response of White Yam (Dioscorea rotundata Poir) Tuber Portions to Positive Selection for Quality Seed Yam Production

Abstract: The production of yams is constrained by high cost and unavailability of clean planting materials, pests and diseases. Vegetative propagation has also caused a build of up diseases, reported to cause up to 80% yield reduction due to scarcity of quality declared seeds. Planting of disease-free material has been found to be effective in reducing disease problems in plants. This study was conducted to produce clean seed yam by reducing yam diseases through positive selection method. In this method, apparently hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
(13 reference statements)
2
5
1
Order By: Relevance
“…Apart from reduction in incidence of mosaic disease, yields of seed yam significantly increased in PS compared to FP options. This agrees with findings of Aihebhoria et al (2017) who worked on the response of white yam tuber portions to Positive Selection for quality seed yam production in Nigeria and found out that in addition to reductions in YMV incidence and severity, fresh tuber weight was significantly higher than control plots. In their study, the authors found out that PS fields recorded a tuber yield of 6.03 t ha -1 compared with 4.99 t ha -1 for FP plots.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Apart from reduction in incidence of mosaic disease, yields of seed yam significantly increased in PS compared to FP options. This agrees with findings of Aihebhoria et al (2017) who worked on the response of white yam tuber portions to Positive Selection for quality seed yam production in Nigeria and found out that in addition to reductions in YMV incidence and severity, fresh tuber weight was significantly higher than control plots. In their study, the authors found out that PS fields recorded a tuber yield of 6.03 t ha -1 compared with 4.99 t ha -1 for FP plots.…”
Section: Discussionsupporting
confidence: 91%
“…3) can be attributed to the accumulation of viruses in farmer saved-seed over multiple cycles of vegetative propagation, the possible exchange of yam materials between farmers and from market sources. This result agrees Aihebhoria et al (2017) that farmer saved seed yam harbor disease pathogens. Galling incidence and index were greater in FP seeds than with PS seeds.…”
Section: Discussionsupporting
confidence: 90%
“…The planting materials used in our trial, including the local variety, were visually selected disease-free tubers from disease-free plants. Work done in IITA on a positive selection with seed yam showed a significant decrease in virus incidence and disease severity score while maintaining reasonably good yields (Aihebhoria et al, 2017). However, we did not index the virus status of the planting materials in our trial and acknowledge the sub-optimal yield of local variety could be a confounded effect of the health status of the variety used in the trial.…”
Section: Discussionmentioning
confidence: 94%
“…Among plants raised from the same mother tuber, some stands were positive for viruses and others were negative. Aiheiboria (2015) reported that plants raised from the head portions of tuber had the highest mean value for incidence and severity of YMV infection while the tail portions were least infected and discussed that as photosynthates flow down to the tuber, they carry along the virus particles. Thus, virus concentration varied with tuber portion, and by extension, it suggests that the smaller the seed tuber portion, the higher the probability of uniformly virus-free progenies from it.…”
Section: Resultsmentioning
confidence: 99%